Cooperating with the police as an act of social control: Trust and neighbourhood concerns as predictors of public assistance - Bradford, B; Jackson, J (Universitetsforlaget, 2016)
Calling upon and assisting police officers are acts that link informal and formal mechanisms of social control. In this paper we draw upon data from a survey of seven London electoral wards to investigate some of the factors predicting public willingness to assist police. We find that such cooperation is associated, first, with high levels of public trust in police, second with confidence that local residents will intervene on behalf of the collective good, and third with heightened concerns about disorder and the loss of authority and discipline in society. We conclude with the idea that cooperation may be influenced not only by peoples’ relationships with police, but also by their (real and imagined) relationships with each other. Notably, police may garner public cooperation when social cohesion is perceived to be high and when there seem to be challenges to the established moral order.